Developing the concept of socially responsible international human resource management - Shen, Jie (Routledge, 2011)
Integrating the literature on international human resource management (IHRM) with corporate social responsibility, this paper introduces the concept of socially responsible IHRM (SRIHRM) and develops its construct in key IHRM functions. This paper also discusses the complexities in the implementation of and the factors that may determine multinational enterprises' decisions regarding SRIHRM practices. Avenues for further research and discussions on the practical implications are suggested.